Effect of Yinian Jiangya Yin on Primary Hypertension in Early Stage --A Clinical Observations on 40 Patients - 赵永华 刘煜德 关莹 刘乃维 (Journal of traditional Chinese medicine, 2010)
Objective： To observe the effect of Yinian Jiangya Yin （Decoction for lowering blood pressure to prolong life） on patients with early hypertension and its mechanism on the function of vascular endotheliocytes. Methods： The 79 patients with early primary hypertension belonging to the TCM syndrome of stagnation of phlegm and blood stasis in meridians and hyperactivity of the liver-yang were randomly divided into a treatment group of 40 patients treated with Yinian Jiangya Yin and a control group of 39 patients treated with Tianma Gouteng Yin （Decoction of Gastrodia and Uncaria）. The changes in score of TCM syndrome and in blood pressure before and after treatment were observed in the two groups. The contents of nitrogen monoxide （NO） and endothelin （ET） in serum after treatment were determined. Results： There was a statistical difference （P〈0.05） in score of TCM syndrome, effect of lowering blood pressure, and the contents of ET and NO in serum after treatment between the two groups. Conclusion： The effect of Yinian Jiangya Yin on improving TCM syndrome of patients with primary hypertension in early stage and on lowering blood pressure may be related to its regulating the imbalanced condition between ET and NO for restoring the function of endothelium-dependent vasodilation.